Does the reduction of regional trade policy uncertainty increase Chinese enterprises' outward foreign direct investment? Evidence from the China−ASEAN Free Trade Area. (28th June 2020) - Sun, Lin; Zhou, Kexuan; Yu, Linhui
Abstract: Regional trade policy uncertainty is an important factor affecting enterprises' outward foreign direct investment (OFDI). This paper uses the China−ASEAN Free Trade Area as the research object. The research uses the "China Industrial Firm Database" from 2001 to 2013 and the "List of Chinese Overseas Investment Enterprises (Institutions)" to match micro‐enterprise data. Using the difference‐in‐difference (DID) approach to construct quasi‐natural experiments, we study the impact of the reduction in regional trade policy uncertainty on Chinese enterprises' OFID. The results show that the free trade agreement strategy implemented by China has reduced the regional trade policy uncertainty, which has had a significant positive impact on Chinese enterprises' OFDI. The establishment of the China−ASEAN Free Trade Area has significantly increased Chinese enterprises' OFID in ASEAN countries. The study further finds that enterprises of different ownership types, in different regions and of different factor intensities display heterogeneous effects in this process. The empirical results of the paper provide new ideas for promoting OFDI from the standpoint of reducing regional trade policy uncertainty, and also provide a new perspective for explaining the increase in foreign investment in China in recent years.